Penjernihan Minyak Jelantah Menggunakan Bleaching Earth dengan Variasi Massa Karbon Tangkai Nipah - Mila Hasna Zalfa; Umar Kalmar Nizar (Lembaga Yasin AlSys, 2026)
Used cooking oil is waste generated from repeated frying that undergoes quality deterioration due to oxidation, hydrolysis, and polymerization reactions, thereby potentially causing adverse effects on health and the environment. One method that can be used to improve the quality of used cooking oil is adsorption using a combination of biomass-derived carbon and bleaching earth. This study aimed to analyze the effect of variations in the mass of nipa palm stalk carbon (Nypa fruticans) combined with bleaching earth on the characteristics of used cooking oil after the purification process. Nipa palm stalk carbon was obtained through carbonization at 300 °C for 1 hour. The purification process was conducted on 100 mL of used cooking oil using carbon mass variations of 1, 3, and 5 g, with a constant bleaching earth mass of 0.5 g. The characteristics of the purified oil were evaluated based on density, flow rate, acid value, and saponification value, whereas the carbon characteristics were analyzed through proximate testing. The proximate analysis results showed that nipa palm stalk carbon had a moisture content of 0.0148%, an ash content of 5.27%, a volatile matter content of 2.5670%, and a fixed carbon content of 92.15%. Increasing the carbon mass from 1 to 5 g reduced the oil density from 0.9326 to 0.9085 g/mL and the acid value from 49.112 to 12.256 mg KOH/g, while increasing the flow rate from 0.795 to 2.18 mL/s and the saponification value from 95.161 to 165.180 mg KOH/g. The best treatment was obtained using a combination of 5 g of nipa palm stalk carbon and 0.5 g of bleaching earth. These findings indicate that increasing the mass of nipa palm stalk carbon in the adsorbent combination improved the physicochemical characteristics of used cooking oil. The combination of nipa palm stalk carbon and bleaching earth has the potential to be developed as a simple, economical, and environmentally friendly biomass-based adsorbent for used cooking oil purification.